Prokaryotic and eukaryotic RNA polymerases have homologous core subunits. - Sweetser, D (1987)
Eukaryotic RNA polymerases are complex aggregates whose component subunits are functionally ill-defined. The gene that encodes the 140,000-dalton subunit of Saccharomyces cerevisiae RNA polymerase II was isolated and studied in detail to obtain clues to the protein's function. This gene, RPB2, exists in a single copy in the haploid genome. Disruption of the gene is lethal to the yeast cell. RPB2 encodes a protein of 138,750 daltons, which contains sequences implicated in binding purine nucleotides and zinc ions and exhibits striking sequence homology with the beta subunit of Escherichia coli RNA polymerase. These observations suggest that the yeast and the E. coli subunit have similar roles in RNA synthesis, as the beta subunit contains binding sites for nucleotide substrates and a portion of the catalytic site for RNA synthesis. The subunit homologies reported here, and those observed previously with the largest RNA polymerase subunit, indicate that components of the prokaryotic RNA polymerase "core" enzyme have counterparts in eukaryotic RNA polymerases.